Computed tomographic scanning of the lung in patients with allergic bronchopulmonary aspergillosis and in asthmatic patients with a positive skin test to Aspergillus fumigatus. Issue 6 (June 1994) - Angus, R M; Davies, M L; Cowan, M D; McSharry, C; Thomson, N C
Abstract : BACKGROUND–Allergic bronchopulmonary aspergillosis is a disease of asthmatic patients which may follow a protracted course and result in chronic lung damage such as central bronchiectasis. In asthma uncomplicated by allergic bronchopulmonary aspergillosis, in particular in asthmatic patients with immediate hypersensitivity type skin reactions to Aspergillus fumigatus, the incidence of bronchiectasis is uncertain. METHODS–Computed tomographic (CT) scans were performed in 17 asthmatic patients of mean (SE) age 60.1 (2.5) years, FEV1 49.4 (5.8)% predicted with allergic bronchopulmonary aspergillosis (all with current or previous positive precipitins to A fumigatus) and in 11 asthmatic patients of mean (SE) age 49.5 (5.8) years, FEV1 75.5 (6.5)% predicted, skin test positive for A fumigatus, but without the clinical or serological features of allergic bronchopulmonary aspergillosis (non-allergic bronchopulmonary aspergillosis group). RESULTS–Bronchial dilatation was more common in the group with allergic bronchopulmonary aspergillosis, affecting 14 patients compared with two in the non-allergic bronchopulmonary aspergillosis group. Evidence of bronchiectasis was found in 43 of a possible 102 lobes of patients with allergic bronchopulmonary aspergillosis, compared with three of a possible 66 in the non-allergic bronchopulmonary aspergillosis group. Bronchial wall thickening was common to both, affecting 16 and nine patients respectively. Pleural thickening on CT scanning was common in the group with allergic bronchopulmonary aspergillosis, being noted in 14 patients compared with only three in the non-allergic bronchopulmonary aspergillosis group. CONCLUSIONS–Bronchiectasis is common in allergic bronchopulmonary aspergillosis but occurs only occasionally in asthmatic patients with a positive skin test to A fumigatus but without other features of the disease.